Clinical progression of autoimmune thyroiditis in children and adolescents treated at the Instituto Nacional de Salud del Niño - Núñez Almache, Oswaldo (2015)
Introduction. Autoimmune thyroiditis is the most common cause of hypothyroidism in children. Clinical diagnosis depends on biochemical condition and monitoring is essential to adopt therapeutic measures and ensure proper growth and development. Objective. To describe the clinical progression of autoimmune thyroiditis in children and adolescents. Design. Retrospective, longitudinal series of cases study. Setting. Department of Endocrinology, Instituto Nacional de Salud del Niño, Lima, Peru (a teaching institution). Participants. Children and adolescents suffering of autoimmune thyroiditis. Interventions. Sixty-five patients -58 women and 7 men- under the age of 18 suffering of autoimmune thyroiditis and admitted between 2000-2012 were followed with clinical and biochemical evaluations over one year; carriers of genetic syndromes or with type 1 diabetes mellitus were excluded. Main outcome measures. Clinical progression of autoimmune thyroiditis. Results. Goiter (78.5%) was a predominant sign and risk factor for development of acquired hypothyroidism in those who debuted with subclinical hypothyroidism. At admission 48% of prepubescent infants presented thyroid dysfunction compared with 26.6% of pubescent subjects. Out of the total population 46% suffered of acquired hypothyroidism, 26% subclinical hypothyroidism, and 23% were euthyroid; 27% of euthyroid patients and 47% of subjects with subclinical hypothyroidism evolved into acquired hypothyroidism. There was no statistically significant difference in the mean Z score for height or BMI at diagnosis nor during follow-up. Conclusions. Children and adolescents with autoimmune thyroiditis debuting as euthyroid or with subclinical hypothyroidism had a high risk of developing acquired hypothyroidism. It seems important to monitor thyroid function for timely initiation of hormone replacement therapy.